Developing Standards for Mosque Design in Lahore, Pakistan - Muhamamd Ilyas Malik; Farah Jamil; Beenish Mujahid (Journal of Islamic Thought and Civilization, 2019)
Mosque has always been the most prestigious and important building for the Muslims.However, no standards or guidelines are available in Pakistan for the design and details of Mosque, therefore, mosques are being designed and built as per the existing examples or personal wisdom of the architects, financers, decision makers, and individuals or groups responsible for its execution. It has been generally observed that there are many flaws found everywhere in terms of plot orientation, placement of different functions of mosque, planning layout , interior spaces , opening of doors/windows, design of ablution area, adequate no. of toilets and shoe storage racks etc. The major problem that worshipers face are related to insufficient width of row (saff) and clearance from walls to perform physical actions of prayer and to carryout ablution in comfortable manner. The aim of this research is to set- out the planning and design guidelines and to develop standards for a religiously and socially acceptable, efficient and comfortable design for all features of a mosque. The methodology includes study of religious literature and survey of existing mosques selected in different localities of Lahore to obtain standards being practiced and comments of end users. Methodology also included physical demonstration to experiment the actual space needed during performance of prayer by worshippers. The paper suggests solutions to some of the issues related to this topic. The developed guidelines/standards would be a source of information for students, practicing architects and academicians. Mosques constructed on the basis of these standards will provide better utilization of space and more comfortable environment to the end users